М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
MrMixa008
MrMixa008
01.09.2021 08:52 •  Математика

(890 - 36*4)*37 - 106*8= 23 146*33-12 146*33-3 174*72=

Заранее

👇
Ответ:
Coolgirl03
Coolgirl03
01.09.2021

Відповідь:

26 754

134 472

Покрокове пояснення:

(890 - 36*4)*37-106*8 = (890 - 144) * 37 - 848= 746*37 - 848 = 27602 - 848 = 26754

23 146 *33 - 12 146*33 - 3 174 * 72 = 763818 - 400818 - 228528 = 134472

4,5(51 оценок)
Открыть все ответы
Ответ:
fgdfc1
fgdfc1
01.09.2021
2x² -3x -9 =0 ;
2x² -6x +3x -9 =0;
2x(x-3) +3(x-3) =0 ;
(x-3)(2x+3) =0 ;
2(x+3/2)(x-3) =0 ⇒[ x+3/2=0 ;x-3 =0 ⇔[  x= - 3/2 ;x=3.
* * *x₁ =-3/2 ; x₂ =3.* * *

5 x²+3х+4=5(x² +(3/5)x +4/5 ) =5(x² +2*(3/10)x +(3/10)² -(3/10)² +4/5 ) =
=5 ((x +3/10)² +71/100) ≠0 →не имеет действительных корней.

3x² -2x-8 =3(x² -2*(1/3)*x +(1/3)² - (1/3)² -8/3) =3*((x-1/3)² -(5/3)²) =
3*(x-1/3 -5/3)(x-1/3 +5/3) =3*(x-2)(x +4/3) .
3x² -2x-8 =0 ⇔3*(x-2)(x +4/3) =0 x⇔[ x-2 =0 ;x +4/3=0⇔[ x=2 ; x = - 4/3.
* * *
3x² -2x-8 =(3x² -6x) +(4x -8) =3x(x-2) +4(x-2) =(x-2)(3x+4) =3(x+4/3)(x-2) .
3x² -2x-8 =0 ⇔3(x+4/3)(x-2) =0 ⇒ [x+4/3=0 ;x-2 =0 ⇔[x= - 4/3 ;x=2 .
* * * x₁ = - 4/3 ;x₂ =2 . * * *
4,5(98 оценок)
Ответ:
MrSasha1111
MrSasha1111
01.09.2021
2x² -3x -9 =0 ;
2x² -6x +3x -9 =0;
2x(x-3) +3(x-3) =0 ;
(x-3)(2x+3) =0 ;
2(x+3/2)(x-3) =0 ⇒[ x+3/2=0 ;x-3 =0 ⇔[  x= - 3/2 ;x=3.
* * *x₁ =-3/2 ; x₂ =3.* * *

5 x²+3х+4=5(x² +(3/5)x +4/5 ) =5(x² +2*(3/10)x +(3/10)² -(3/10)² +4/5 ) =
=5 ((x +3/10)² +71/100) ≠0 →не имеет действительных корней.

3x² -2x-8 =3(x² -2*(1/3)*x +(1/3)² - (1/3)² -8/3) =3*((x-1/3)² -(5/3)²) =
3*(x-1/3 -5/3)(x-1/3 +5/3) =3*(x-2)(x +4/3) .
3x² -2x-8 =0 ⇔3*(x-2)(x +4/3) =0 x⇔[ x-2 =0 ;x +4/3=0⇔[ x=2 ; x = - 4/3.
* * *
3x² -2x-8 =(3x² -6x) +(4x -8) =3x(x-2) +4(x-2) =(x-2)(3x+4) =3(x+4/3)(x-2) .
3x² -2x-8 =0 ⇔3(x+4/3)(x-2) =0 ⇒ [x+4/3=0 ;x-2 =0 ⇔[x= - 4/3 ;x=2 .
* * * x₁ = - 4/3 ;x₂ =2 . * * *
4,4(28 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ